Proceedings of the 4th International Conference on Higher Education Advances (HEAd'18) 2018
DOI: 10.4995/head18.2018.8184
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Social Innovation in Latin America Academic Curriculum

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Rubens et al (2017) in their literature review conclude that some faculty members "still see the third mission as a waste of time or something that can only be done after they have completed their academic duties" (p. 364). Similarly, other studies report of a lack of individual interest in social innovation among staff and students at HEIs and a corresponding resistance (Galego et al, 2018;Henderson et al, 2019).…”
Section: Individual Attitudes Towards Social Innovation and Third Mission At Higher Education Institutesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rubens et al (2017) in their literature review conclude that some faculty members "still see the third mission as a waste of time or something that can only be done after they have completed their academic duties" (p. 364). Similarly, other studies report of a lack of individual interest in social innovation among staff and students at HEIs and a corresponding resistance (Galego et al, 2018;Henderson et al, 2019).…”
Section: Individual Attitudes Towards Social Innovation and Third Mission At Higher Education Institutesmentioning
confidence: 99%
“…They describe two categories of barriers: firstly, external barriers, such as difficulties with government regulations and funding allocation; secondly, internal barriers related to the organizational characteristics of the universities and partner organizations. Structural barriers and challenges are reported in numerous studies on social innovation and third mission at higher education institutions, such as the lack of policy frameworks and management support (Galego et al, 2018;, as well as institutional barriers, including a lack of resources and reward systems (Hazenberg et al, 2019;Siegel et al, 2003), and the incompatible expectations or demands of external partners (Schartinger et al, 2001). These obstacles are known to some extent from previous social innovation projects or social enterprises outside the higher education sector.…”
Section: Individual Attitudes Towards Social Innovation and Third Mission At Higher Education Institutesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the project reveals that Latin American HEIs have developed compulsory courses, extra-curricular programmes and a variety of methodologies, teaching and learning tools, and research topics in the field of social innovation and entrepreneurship. In fact, through a questionnaire addressed to the coordinators of the 10 Latin American universities participating in the project, we could identify a total of 48 courses (42 undergraduate and 6 postgraduate) which were framed in various disciplines and areas of knowledge [32], and many of them were taught as voluntary subjects. The multiplicity of areas of study reported could be explained, indeed, by the diversity of definitions and approaches to social innovation and social entrepreneurship within the participating universities, something that according to Galego et al (2018) [32] could lead to an inadequate classification of the courses.…”
Section: Si and Se In Latin American Heismentioning
confidence: 99%
“…While acknowledging the difficulties and complexities of the South African economy (Rodriguez and Rodriguez, 2015), the study also adds to the literature by examining chemical scientists' experiences of social innovation and investigating what could be added to the usual science degree offerings to enhance their professional success. It thus offers an understanding of how social innovation could impact the curricula of chemical science degrees (Galego, Soto, Carrasco, Amorim, and Ferreira Dias, 2018b). In particular, it lays the foundation for the development of a theoretical framework to explain the impact of social innovation education on chemical scientists by examining it from the participants' perspectives.…”
Section: Introductionmentioning
confidence: 99%